Efektifitas Penerapan Latihan Shuttle Run terhadap Kelincahan Atlet Kumite Karate SKO Provinsi Riau - Salsabilah, Salsabilah; Diyanto, Rahmad; Hilmi Wahdi, Agung; Syaputra, Aidil; Evriansyah Lubis, Ade (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2025)
This research aims to know the effect of shuttle run training (X) on the Agility (Y) of Kumite athletes at the Karate SKO Riau. The method used in this research is an experimental method, with the research design used in this study is